Analysis of Non Physical Work Environment, Reward, Punishment and the Influence on Work Discipline of Employee - Setyovani Nurfitri Wahyuningrum; Yuli - Sudarso; Jumi - Jumi (Politeknik Negeri Semarang, 2020)
Work discipline probleme of employee of PT Wahana Sun Motor Semarang Indomobil Nissan Setiabudi can be seen from fluctuating attendance level. The purpose of this research was to analyze the influence of non physical work environment, reward and punishment on work discipline partially and simultaneously. Analysis used in this study was descriptive and quantitative. The data was collected using a quationnair, interview and literature. The data was analyzed by multiple linear regression. The number of respondents in this research was 30 employees. Statistic analysis result showed that non physical work environment partially hasn’t significant influence on work discipline. In the other hand reward and punishment have significant influence on work discipline. Simultaneously non physical work environment, reward and punishment have significant influence on work discipline. Based on multiple linear regression equation calculates, obtained the equation Y= 3,233 + 0,013 X1 + 0,346 X2 + 0,312 X3. Work discipline was explained by non physical work environtment, reward and punishment by 40,1% while 59,9% were explained by other variables were not researched.